A comprehensive review of distributed power system architecture for telecom and datacenter applications - Ramesh B. Darla; Chitra A (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
With the dominating utility of the internet, it becomes critical to manage the efficiency and reliability of telecom and datacenter, as the power consumption of the involved equipment also increases. Much power being wasted through the power conversion stages by converting AC voltage to DC voltage and then stepping down to lower voltages to connect to information and communication technology (ICT) equipment. 48/12 VDC is the standard DC bus architecture to serve the end utility equipment. This voltage level is further processed to multiple lower voltages to power up the internal auxiliary circuits. Power losses are involved when it is converted from higher voltage to lower voltages. Therefore, the efficiency of power conversion is lower. There is a need to increase the efficiency by minimizing the power losses which occur due to the conversion stages. Different methods are available to increase the efficiency of a system by optimizing the converter topologies, semiconductor materials and control methods. There is another possibility of increasing the efficiency by changing the architecture of a system by increasing the DC bus voltage to higher voltages to optimize the losses. This paper presents a review of available high voltage options for telecom power distribution and developments, implementations and challenges across the world.